The role of Islamic Education Institutions in Religious Moderation in The Communities of Perbutulan Village - Harsela, Chiska Nova (Devotion : Journal of Research and Community Service, 2021)
The education of Islamic education institutions in Perbutulan Village, Sumber District, Cirebon Regency plays a role in moderate religious education, influencing changes in social and religious behavior in people's lives as well as on priority fiqh problems. The method used in this research is descriptive qualitative method by collecting data through interviews with those involved in Islamic education institutions and filling out online questionnaires to the people of Perbutulan community. The results of this study conclude that the role of Islamic education institutions in Perbutulan Village towards religious moderation is as an introduction that in religion one must respect one another, practice religion according to the guidance of the Al-Qur'an and sunnah. The Perbutulan community does not debate the differences between fiqh that exist in the Perbutulan community. With the existence of Islamic education institutions in Perbutulan, it can help the community in carrying out daily life with religious knowledge that has been taught.